2010
DOI: 10.1177/1534735410378660
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sesquiterpenes Isolated From Largehead Atractylodes Rhizome on Growth, Migration, and Differentiation of B16 Melanoma Cells

Abstract: The aims of this study were to isolate sesquiterpene compounds from the largehead atractylodes rhizome (LAR) and to investigate their effects on B16 cancer cells. A total of 8 sesquiterpenes from LAR were identified, of which eudesm-4 (15), 7-diene-9a, 11-diol (7) was isolated for the first time. All 8 compounds inhibited growth of B16 cells, and atractylenolide I (AT-I), atractylenolide II (AT-II), and atractylenolactam (ATR) were the most potent, with IC 50 values of 76.46, 84.02, and 54.88 mΜ, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…ATR exhibits a wide range of biological and pharmacological activities, such as anti-inflammatory, neuroprotection and gastroprotective effects [ 5 7 ]. Among the three members of ATR, ATR-1 exerts the best anti-tumor activity [ 8 , 9 ]. For example, ATR-1 was able to trigger apoptosis and cell cycle arrest in melanoma cells as well as lung carcinoma cells in vitro [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…ATR exhibits a wide range of biological and pharmacological activities, such as anti-inflammatory, neuroprotection and gastroprotective effects [ 5 7 ]. Among the three members of ATR, ATR-1 exerts the best anti-tumor activity [ 8 , 9 ]. For example, ATR-1 was able to trigger apoptosis and cell cycle arrest in melanoma cells as well as lung carcinoma cells in vitro [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In our in vitro experiment, treatment with both URAM and FRAM resulted in a marked suppression of lipid accumulation in differentiated 3T3-L1 cells, which are widely used as a model of adipogenesis 55 due to their potential capacity for differentiation from fibroblasts to adipocytes 56 . Previous studies have reported that RAM and its active components, including atractylenolide I, atractylenolide II, and atractylon inhibit adipogenesis via the PI3K/Akt signaling pathway 20 57 . Notably, in our study, no marked difference in the degree of inhibition of lipid accumulation was observed between URAM and FRAM-treated cells, implying that fermentation-mediated constitutional changes did not improve the anti-adipogenic activity of RAM.…”
Section: Discussionmentioning
confidence: 99%
“…A potential cancer treatment is to promote cancer cell differentiation, and thereafter, to reduce its proliferative capacity: this approach is a novel therapeutic method aiming to modify tumor cells to a slower rate of proliferation, and thus which leads to the loss of its earlier neoplastic attributes [25,26]. In melanoma, the differentiation status of cells could be monitored by melanogenesis, which resulted in the conversion of l -tyrosine to l- dopa by tyrosinase [27]. Indeed, the levels of melanin and tyrosinase are being considered as indicators of differentiated melanoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Lupeol, a lupine-type triterpene from Danelion root, showed significant inhibition on melanoma cell growth both in vitro and in vivo: the effect was trigged by its induction on cell differentiation [31]. Ye [27] reported that three sesquiterpenes, isolated from the largehead atractylode rhizome, induced melanoma cell differentiation and inhibited cell migration through inactivating the signals of Ras/ERK MAPK (for AT-I and AT-II) and PI3K/AKT. Here, we isolated and identified several prenylated flavonoids including isoflavone, flavone, chalcone, and coumarin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation